2019
DOI: 10.1126/scitranslmed.aax9364
|View full text |Cite
|
Sign up to set email alerts
|

An innate-like Vδ1 + γδ T cell compartment in the human breast is associated with remission in triple-negative breast cancer

Abstract: Innate-like tissue-resident γδ T cell compartments capable of protecting against carcinogenesis are well established in mice. Conversely, the degree to which they exist in humans, their potential properties, and their contributions to host benefit are mostly unresolved. Here, we demonstrate that healthy human breast harbors a distinct γδ T cell compartment, primarily expressing T cell receptor (TCR) Vδ1 chains, by comparison to Vδ2 chains that predominate in peripheral blood. Breast-resident Vδ1+ cells were fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
135
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(146 citation statements)
references
References 91 publications
11
135
0
Order By: Relevance
“…Vδ1 TILs in breast cancer were shown to suppress αβ T cells, 104 whereas a recent study actually identified innate-like Vδ1 TILs as being associated with remission in triple-negative breast cancer. 106 We conclude that the protumorigenic potential of γδ T cells must be well taken into account; however, there is a substantial body of evidence supporting the notion that γδ T cells are exceptional candidates for cellular immunotherapy.…”
Section: Tumor-infiltrating γδ T Cells: Friends or Foes?mentioning
confidence: 77%
“…Vδ1 TILs in breast cancer were shown to suppress αβ T cells, 104 whereas a recent study actually identified innate-like Vδ1 TILs as being associated with remission in triple-negative breast cancer. 106 We conclude that the protumorigenic potential of γδ T cells must be well taken into account; however, there is a substantial body of evidence supporting the notion that γδ T cells are exceptional candidates for cellular immunotherapy.…”
Section: Tumor-infiltrating γδ T Cells: Friends or Foes?mentioning
confidence: 77%
“…γδ T cells, particularly those residing within extralymphoid tissues, have been increasingly implicated in the regulation of tissue maintenance and protection against cancer [39][40][41][42][43][44] . Nonetheless, the cells' biologies remain poorly elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of TCR repertoires proposed that presumably lung-infiltrating Vδ1 + T cells underwent an adaptive-like clonal expansion during active tuberculosis [92]. In contrast, tissue-resident NKG2D + and CD69 + Vδ1 + T cells were reported to have oligoclonal TCR repertoires in healthy breast tissues that remained stable after tumor-infiltration, consistent with their innate-like features such as NKG2D-driven activation [108,109].…”
Section: Tissue-resident γδ Tcr Repertoiresmentioning
confidence: 96%